E-Business Strategies and Digital Marketing Practices – Literature Review - Depi, Jeanne Nurtami; Sari, Yulia Puspita; Chintiyani, Fitri; Sari, Rahmi Rachmawati; Redjeki, Finny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The rapid growth of digital technology has transformed the landscape of business operations. E-business strategies and digital marketing practices have become essential for achieving competitiveness, customer engagement, and market expansion. This literature review aims to explore and analyze the key components, trends, and implications of e-business strategies and digital marketing practices. By synthesizing findings from various academic sources, this study identifies common themes and emerging innovations in the field. The results show that successful e-business strategies are built on agility, customer-centricity, and data-driven decision-making, while digital marketing is increasingly personalized and omnichannel in nature. The review contributes to the understanding of how businesses adapt their models in the digital economy.